The Clinical and Pathological Presentation of Thyroid Nodules in Children and the Comparison with Adult Population: Experience of a Single Institution - Tamas Solymosi; Gyula Lukacs Toth; Laszlo Budai; Istvan Gal (International Journal of Endocrinology)
The clinical and pathological presentation of thyroid nodules among younger and adult patients was compared in an iodine-deficient (ID) region. Data of 3,010 consecutive patients younger than 20 years and 3,010 patients older than 20 years were compared. The proportion of nodular goiters (22.8% versus 39.3%), the ratio of surgically treated nodules (33.2% versus 15.2%), and the proportion of malignant nodules (4.3% versus 2.1%) among diseased patients differed significantly between the two groups (younger versus adult). Nine papillary and 1 medullary carcinoma were found among children, while 15 papillary, 2 follicular, 1 insular, 1 anaplastic, and 1 medullary carcinomas occurred among adults. The ratio of follicular adenoma to hyperplastic nodules (3 : 1 to 1 : 1.67), the proportion of follicular variant (77.8% versus 26.7%), T4 tumors (77.8% versus 33.3%), and tumors with lymph node metastasis (88.9% versus 66.7%) were significantly higher among younger papillary carcinoma patients. No malignancies occurred among spongiform and central type cysts. Similarly to iodine-sufficient regions, more nodules are malignant and carcinomas have a clinically more aggressive presentation in children in comparison with adult patients in ID. Taking the significantly greater proportion of adenomas and the lack of follicular carcinoma into account, a conservative approach has to be considered in follicular tumors among children.